2023
DOI: 10.1371/journal.pntd.0011788
|View full text |Cite
|
Sign up to set email alerts
|

Re-examination of the risk of dementia after dengue virus infection: A population-based cohort study

Yu-Wen Chien,
Hsin-I Shih,
Yu-Ping Wang
et al.

Abstract: Dengue infection can affect the central nervous system and cause various neurological complications. Previous studies also suggest dengue was associated with a significantly increased long-term risk of dementia. A population-based cohort study was conducted using national health databases in Taiwan and included 37,928 laboratory-confirmed dengue patients aged ≥ 45 years between 2002 and 2015, along with 151,712 matched nondengue individuals. Subdistribution hazard regression models showed a slightly increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…A more recent study showed that there were slightly increased risks of non-vascular and overall dementia in dengue patients [19]. We did not know whether dementia was associated with post-dengue frailty.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…A more recent study showed that there were slightly increased risks of non-vascular and overall dementia in dengue patients [19]. We did not know whether dementia was associated with post-dengue frailty.…”
Section: Discussionmentioning
confidence: 83%
“…A study from Belize reported weakness and loss of appetite as the main manifestation of dengue in the geriatric population [18]. And another study in Taiwan showed a higher risk of dementia after dengue infection [19]. However, there is no relevant article describing in detail the frailty status and functional decline in geriatric patients during the timeline of dengue infection.…”
Section: Introductionmentioning
confidence: 99%